ANALYSIS OF THE INFLUENCE OF TALENT MANAGEMENT ON ORGANIZATIONAL INNOVATION WITH ARTIFICIAL INTELLIGENCE (AI) AS AN INTERVENING VARIABLE IN INDONESIA - Kumala Vera Dewi; Azriel Situmorang; Raysal Januar Siregar (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of talent management on organizational innovation with artificial intelligence (AI) as an intervening variable in Indonesia. The background of this study is based on the importance of strategic human resource management in driving organizational innovation in the era of digital transformation. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected by distributing questionnaires to respondents from various organizations in Indonesia that have implemented talent management systems and AI technology. The results of the study indicate that talent management has a significant effect on organizational innovation, both directly and through artificial intelligence as a mediator. This finding strengthens the argument that organizations that manage talent effectively will be better able to adopt intelligent technology and ultimately create sustainable innovation. The role of AI as an intervening variable has been shown to strengthen the relationship between talent management and organizational innovation. This study provides theoretical contributions to the development of human resource and technology management, as well as practical implications for policy making in driving organizational digital transformation.